2011
DOI: 10.1002/ajmg.a.33510
|View full text |Cite
|
Sign up to set email alerts
|

Hajdu–Cheney syndrome with severe dural ectasia

Abstract: Hajdu-Cheney syndrome (HCS) is an autosomal dominant condition comprising osteolysis of the terminal phalanges, characteristic craniofacial abnormalities, dental anomalies, and proportionate short stature. The clinical and radiological findings develop and progress with age. Here, we report on a HCS patient with severe scoliosis and exceptionally massive dural ectasia. Congenital scoliosis and dural ectasia have not been reported previously in HCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 13 publications
(14 reference statements)
5
33
0
Order By: Relevance
“…''Coarse hair'' seen in the patient reported by Avela et al [2011] was shown and commented on in patient 2 included in Gripp et al [1997]. Similarly, the slender built with small muscle mass and little subcutaneous fat shown in Figure 2 in Avela et al [2011] strongly resembles that of patient 2 of Gripp et al [1997].…”
Section: To the Editormentioning
confidence: 78%
See 2 more Smart Citations
“…''Coarse hair'' seen in the patient reported by Avela et al [2011] was shown and commented on in patient 2 included in Gripp et al [1997]. Similarly, the slender built with small muscle mass and little subcutaneous fat shown in Figure 2 in Avela et al [2011] strongly resembles that of patient 2 of Gripp et al [1997].…”
Section: To the Editormentioning
confidence: 78%
“…Table I compares the findings in the patient reported by Avela et al [2011] to those previously published in lateral meningocele syndrome.…”
Section: To the Editormentioning
confidence: 88%
See 1 more Smart Citation
“…Despite the pronounced skeletal abnormalities reported in Hajdu Cheney syndrome, little is known regarding the mechanisms underlying the bone loss or the effects of Notch2 gain-of-function in the skeleton. Information obtained from iliac crest bone biopsies has been inconclusive and reported in a small number of subjects with Hajdu Cheney syndrome (32)(33)(34)(35).…”
Section: Notch2mentioning
confidence: 99%
“…Despite the pronounced skeletal abnormalities reported in Hajdu Cheney syndrome, little is known regarding the mechanisms underlying the bone loss or the effects of Notch2 gain-of-function in the skeleton. Information obtained from iliac crest bone biopsies has been inconclusive and reported in a small number of subjects with Hajdu Cheney syndrome (32)(33)(34)(35).The purpose of this work was to gain understanding on the Hajdu Cheney syndrome skeletal phenotype and the mechanisms involved. To this end, we created a mouse model reproducing the NOTCH2 mutation (6949C3 T) found in a subject affected by the disease and presenting with pronounced osteoporosis and fractures (28,30 …”
mentioning
confidence: 99%